MRI findings of intraductal papillary mucinous neoplasms (IPMNs) - Lana, Silvia; Vallara, Manuela; Bono, Nicola Emanuele; Russo, Giuseppe; Artioli, Giulia; Capretti, Giovanni; Paladini, Ilaria; Pesce, Antonella; Ruggirello, Margherita; Barbalace, Sandro; Mostardi, Maurizio (Acta Biomedica Atenei Parmensis, 2016)
Cystic lesions of the pancreas are relatively frequent imaging findings due to the improvement of imaging technologies. They may be secondary to both benign and malignant disease processes and their prevalence increases with age. In most cases, these lesions are detected incidentally by computed tomography and magnetic resonance imaging (MRI) performed for other reasons. Intraductal papillary mucinous neoplasms (IPMNs) represent 25% of the cystic neoplasms, morphologically classified into “main pancreatic duct IPMN” (MPD-IPMN), “side branches IPMN” (SB-IPMN) and mixed forms. Magnetic Resonance Cholangiopancreatography (MRCP) is a multiparametricity not invasive radiological technique that doesn’t use ionizing radiation or organ iodinized contrast agents; it allows an accurate characterization of the lesions (number and size of cystic lesions, internal features of a cyst, ducts dilation, communication with main pancreatic duct) that is important to guide the differential diagnosis and establish a correct follow-up. International guidelines consider IPMN of MPD and mixed forms to be an indication for surgery, while clinical and radiological follow-up is indicated in asymptomatic patients with SB-IPMN, especially when lesions are < 2,5-3 cm in diameter and there are no mural nodules or dilation of MPD.